Methylation Pattern of the SOCS3 and IL6R Promoters in Rheumatoid Arthritis. (31st March 2020) - Cieśla, Marek; Kolarz, Bogdan; Majdan, Maria; Darmochwał-Kolarz, Dorota
Abstract : Interleukin-6 (IL-6) plays an essential function in the development of rheumatoid arthritis (RA), mainly through its proinflammatory effect, which may lead to joint destruction. The genes encoding IL-6 receptor ( IL6R ) and suppressor of cytokine signaling 3 ( SOCS3 ) play a key role in the IL-6 signaling pathway, but their epigenetic regulation remains unclear. The aim of the study was to investigate how the presence of methylation in the SOCS3 and IL6R promoters is associated with the morbidity and severity of RA. A total of 146 unrelated individuals, 122 with RA and 24 healthy controls, were enrolled in the study. All subjects were genotyped with regard to the rs4969168 and rs4969170 polymorphisms in the SOCS3 gene and the rs2228145 and rs4129267 polymorphisms in IL6R . The methylation study included 52 patients with RA and 24 healthy controls. Qualitative real-time methylation-specific PCR was used to evaluate methylation status. We found no differences between patients and healthy controls in the methylation pattern in the IL6R and SOCS3 promoter regions and in variants frequency. The methylation profiles of the SOCS3 and IL6R promoters do not support the hypothesis that the genes SOCS3 and IL6R involved in the JAK-STAT signaling pathway are epigenetically deregulated in whole blood.